Perjalanan Spiritual Homo Viator: Studi Komparatif Serat Jatimurti dengan Perumpamaan tentang Anak yang Hilang (Luk. 15:11â€“32) - Chandra, Robby (Veritas : Jurnal Teologi dan Pelayanan, 2021)
The Spiritual Journey of Homo Viator: A Comparative Study of Serat Jatimurti with the Parable of the Prodigal Son (Luke 15:11â€“32). The concept of spiritual journey is known in various religions. Likewise, the concept of Homo Viator or humans who made the trip. This paper examines the concept of a spiritual journey in Serat Jatimurti, one of the Kejawen texts, and compares it with the narrative in the Bible, namely the parable of the prodigal son. This study aims to understand the voice of the local spirituality to facilitate the delivery of the gospel to this community. By using cognitive linguistic analysis, the results show some similarities and differences in the Christian view of the spiritual journey and the role of humans in it compared to the Kejawen view. The similarities that exist will increase unÂderstanding and appreciation of each spirituality work and become a common ground that provides an effective â€œbridgeâ€ for sharing the gospel. The differences that exist can be an attraction to show the uniqueness of the gospel. With this understanding, this study can provide provisions for Christians in communicating the good news of Godâ€™s grace in Christ Jesus to the followers of Kejawen spirituality.